2016
DOI: 10.1371/journal.pone.0153561
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Antimicrobial Resistance and Genetic Diversity of Klebsiella pneumoniae in Food Samples

Abstract: This study aimed to assess the frequency of Klebsiella pneumoniae in food samples and to detect antibiotic resistance phenotypes, antimicrobial resistance genes and the molecular subtypes of the recovered isolates. A total of 998 food samples were collected, and 99 (9.9%) K. pneumoniae strains were isolated; the frequencies were 8.2% (4/49) in fresh raw seafood, 13.8% (26/188) in fresh raw chicken, 11.4% (34/297) in frozen raw food and 7.5% (35/464) in cooked food samples. Antimicrobial resistance was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
54
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 55 publications
12
54
3
6
Order By: Relevance
“…The presence of K. pneumoniae in fish and shrimp samples ( Table 1 ) serves as an alert and the health risks presented by these strains should not be underestimated. Some studies corroborate the present investigation since they reported the isolation of these species from fish, seafood and other types of food 18 , 19 .…”
Section: Discussionsupporting
confidence: 91%
“…The presence of K. pneumoniae in fish and shrimp samples ( Table 1 ) serves as an alert and the health risks presented by these strains should not be underestimated. Some studies corroborate the present investigation since they reported the isolation of these species from fish, seafood and other types of food 18 , 19 .…”
Section: Discussionsupporting
confidence: 91%
“…1 This bacterium is the cause of hospital-acquired infections such as bloodstream infections, pneumonia, meningitis, sepsis, infections in newborns, and intensive care unit patients. 2 In the last decade, the rate of morbidity and mortality related to these infections has increased. 3 The incidence and mortality rates were reported as 7.1 per 100,000 per year and 1.3 per 100,000 per year, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The threat due to the presence of enteric pathogens in seafood is more confounding when such bacteria are multi-drug resistant (MDR). The prevalence of MDR bacteria in seafood has been reported in many studies in the recent past [ 19 , 20 , 21 , 22 , 23 ]. The antibiotic resistance patterns of clinical isolates of enteric bacteria is alarmingly high in India and with the discovery of NDM-producing enteric bacteria, the concerns on the rapid spread of such bacteria via food chain and water is increasing [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%